2017
DOI: 10.1039/c6fd00155f
|View full text |Cite
|
Sign up to set email alerts
|

Development of solid-state emissive o-carboranes and theoretical investigation of the mechanism of the aggregation-induced emission behaviors of organoboron “element-blocks”

Abstract: This paper presents the aggregation-induced emission (AIE) properties of o-carborane derivatives and proposes a potential strategy for constructing AIE-active organoboron complexes via the enhancement of freedom of intramolecular mobility. Initially, the optical properties of o-carborane derivatives with or without the fused ring structure at the C-C bond in o-carborane in which elongation should be induced by photo-excitation according to theoretical calculations were compared. Accordingly, it was shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 77 publications
0
42
0
Order By: Relevance
“…Furthermore, some of them show AIE behavior , . We also found several AIE‐inducible “element‐blocks” and applied these molecules for functional solid‐state luminescent materials such as film‐type chemical sensors,, molecules showing crystallization‐induced emission, luminescent chromic bioprobes for volatile organic molecules, thermochromic substances,, and mechanochromic luminescent materials, especially based on chromic luminescence behavior originated from morphology changes in the condensed state . Although clear color changes were induced in these materials in response to the target stimuli, emission intensity changes were often critically lowered by the changing morphology in the solid state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some of them show AIE behavior , . We also found several AIE‐inducible “element‐blocks” and applied these molecules for functional solid‐state luminescent materials such as film‐type chemical sensors,, molecules showing crystallization‐induced emission, luminescent chromic bioprobes for volatile organic molecules, thermochromic substances,, and mechanochromic luminescent materials, especially based on chromic luminescence behavior originated from morphology changes in the condensed state . Although clear color changes were induced in these materials in response to the target stimuli, emission intensity changes were often critically lowered by the changing morphology in the solid state.…”
Section: Introductionmentioning
confidence: 99%
“…Herein we present the development of luminescent boron complexes and color‐tuning of their luminescence without changes in their emission efficiency. On the basis of the strategy to obtain constant intense emission from AIE‐active boron ketoiminate both in solution and the solid state, boron complexes with fused ligands were designed for fixing molecular motions completely. To confirm the validity of this idea, we designed the molecules and evaluated their optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Intense solid-state luminescent properties originating from AIE were found and applied for developing the conjugated materials, including polymers. [37][38][39][40] The o-carborane cluster is a boron cluster composed of three-center two-electron bonds, and acts as a strong electron-withdrawing group over, it was shown that the efficiency of DCB-tBu was over 0.70 in the amorphous state. [5][6][7] It has been reported that some of the o-carborane [8][9][10][11][12][13] derivatives presented AIE [14][15][16][17][18][19][20][21] and can be applied as a solid-state luminescent material.…”
Section: Introductionmentioning
confidence: 99%
“…86 To understand the origin of this drastic change in the optical properties, we performed theoretical calculations to estimate the optimized structures. 106 Significantly, by comparing the structure in the ground state obtained from density-functional theory with the result from the density-functional theory organic comp calculation, which can provide the structural information on the excited state, it was suggested that a larger degree of structural relaxation should proceed in the AIE-active boron complex. It is reasonable that excitation energy should be effectively dissipated by vigorous molecular motions in the solution state, followed by emission annihilation.…”
Section: Scheme 2 Syntheses Of Bisphosphines (Ss)-3-bh 3 and (Rr)-3mentioning
confidence: 99%
“…The final topic on group 13 element-blocks is on the logical design of AIE-active molecules with theoretical calculations based on 'flexible' boron complexes. 106 From the first report on the AIE-active silole derivative in 2001, significant efforts have been dedicated to developing functional luminescent materials based on AIE-active molecules. Moreover, new molecules possessing AIE and/or other types of enhanced emission properties in the solid state have been continuously discovered.…”
Section: Scheme 2 Syntheses Of Bisphosphines (Ss)-3-bh 3 and (Rr)-3mentioning
confidence: 99%